Post‐consumer recycled high density polyethylene/polypropylene blend with improved overall performance through modification by impact polypropylene copolymer: morphology, properties and fracture resistance. Issue 12 (30th June 2021) - Mehrabi‐Mazidi, Majid; Sharifi, Hossein
Abstract: The effect of an impact polypropylene copolymer (IPC) having excellent stiffness–toughness balance on the microstructure and properties of a blend comprising 80 wt% recycled high density polyethylene (rHDPE) and 20 wt% recycled isotactic polypropylene (rPP) was studied. Morphological observations revealed improved interfacial interactions, a finer dispersion state and a more homogeneous phase morphology upon IPC incorporation into the blend up to 20 wt%. Flexural modulus, flexural strength, tensile strength and tensile ductility were steadily increased with IPC loading, and exhibited 13%, 14%, 35% and 520% improvement at 20 wt% IPC. A monotonic rise in Izod impact energy, accompanied by a transition from semi‐brittle to fully ductile failure mode, was observed with IPC concentration, so that this parameter showed 110% increment at 20 wt% IPC. The change in properties was attributed to the compatibilization, toughening as well as reinforcing effects of the IPC phase in the modified blends. Melting and crystallization of the blends were studied by the DSC technique. Failure mechanisms and micro‐deformations accompanying the impact fracture process of the blends were closely examined, and the role of IPC in improving the toughness and fracture resistance of the modified blends was clarified. The results were interpreted in terms of interfacial strength, efficiency of stress transfer across the phase boundaries, and stability of plastic micro‐deformations during the fracture process. The results clearly demonstrate that simultaneous improvement in stiffness, strength and (impact) toughness of the incompatible rHDPE/rPP blend can be achieved by modification with a properly chosen IPC. The present work addresses some challenges, with respect to stiffness and strength, encountered with the use of conventional elastomeric and/or plastomeric olefin copolymers as common modifiers for polyolefin blends. © 2021 Society of Industrial Chemistry. Abstract : Modification of recycled high density polyethylene/recycled isotactic polypropylene (rHDPE/rPP) (80/20) blend by an impact polypropylene copolymer having excellent stiffness–toughness balance promoted effective compatibilization with simultaneous improvement in stiffness, strength and impact performance of the resulting blend.